Penanggulangan Terhadap Masyarakat Korban Banjir Rob Yang Menimpa Empat Kecamatan di Kota Semarang Jawa Tengah - Dewi Tjandraningsih (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
The aim of this research is to determine the objective condition of flood victims in Semarang City. Management of flood victims that hit four sub-districts. The research method uses a qualitative approach that describes phenomena and events at the location of flood victims. Data collection techniques were obtained through interviews with several victims, several community association administrators, observations at flood locations by observing residents who were affected by the flood. Literacy studies related to flood victims, in the form of documentation, mass media and online media and the internet. Conclusion Conditions that occur due to extreme weather, strong gusts of wind and non-stop rain for twenty-four hours in the city of Semarang. Covered four sub-districts, namely Pedurungan, North Semarang, Genuk and Gayamsari. And also the tidal sea level, flooding the Kaligawe highway, causing it to become unstable and large trucks breaking down. The Semarang City Government has responded to the impact of the flood by sending aid in the form of drinking water, basic necessities and food to the community, the Semarang Fire Department has also evacuated the elderly and sick people to be able to take refuge at relatives' homes and to hospitals to receive medical treatment at the hospital. Semarang City General.